Assessment of Duodenal Diverticula: Computed Tomography Findings - Yilmaz, Erdem; Kostek, Osman; Hereklioglu, Savas; Goktas, Muhammet; Tuncbilek, Nermin (Current Medical Imaging, 2019)
Aims: To demonstrate the prevalence, accompanying pathologies, imaging and follow up findings of Duodenal Diverticula (DD) with Multidetector Computed Tomography (MDCT). Materials and Methods: Consecutive 2910 abdominal MDCTs were retrospectively reviewed on axial, coronal and sagittal planes. DD were evaluated for prevalence, location, number, size, contents, diverticular neck, accompanying pancreaticobiliary pathologies, jejunal and colonic diverticula, respectively. Results: DD were diagnosed in 157 cases (5.4%) and found mostly in the second part of the duodenum. Juxta-ampullary DD was the most common type (78.3%) and mostly located ventral (n:86, 69.9%) to the ampulla of Vater. DD was solitary in 123 patients (78.3%) and more than one in 34 patients (21.7%). The median diameter of DD was 2.5 cm (range 1.5-3.6 cm) in the long-axis. The lumen of DD contains air and contrast agent (n:96, 61.1%); air, contrast agent and debris (n:42, 26.7%) in most cases. Colonic diverticula (n:36, 22.9%), cholelithiasis (n:32, 20.4%), choledocholithiasis (n:7, 4.4%), and biliary dilatation (n:8, 5.1%) were the most common additional findings. Median follow-up time was 23 months (range 11 to 41 months). In three cases, new findings (cholelithiasis, n:3, choledocholithiasis, n:1) were detected. Conclusion: Accompanying pathologies with DD diagnosis are valuable for physicians in order to manage the patients. Following clinical and radiological features of well-diagnosed DD might reduce the possible complications.
Keywords: cholelithiasis